Shedding light on a species from the shadows: the case of Paepalanthus macaheensis (Eriocaulaceae) - Trovó, Marcelo; Sano, Paulo (Phytotaxa, 2015)
Open grasslands are the usual habitats of Eriocaulaceae, but a few species also grow in forest understory. Paepalanthus macaheensis grows exclusively in shaded habitat, and has broad morphological variation and a confusing taxonomy. Here, the nomenclatural history associated with this species is clarified, the name is formally reestablished, and a second-step lectotype for the name is designated. Paepalanthus euryphyllus is proposed as a new synonym of P. macaheensis and comparisons with morphologically similar species are presented. A detailed description, the first line drawings of P. macaheensis, photographs, and a distribution map are provided. An official conservation status of endangered was assessed by the Brazilian National Center for Flora Conservation (CNCFlora).